LVP vs TIPS for Refractory Ascites: Where Do We Stand? - Varma, Rakesh K.; Singh, Karan Bir; Bready, Eric; Singh, Deepak; Caridi, Theresa M.; Shoreibah, Mohamed (Digestive Disease Interventions, 2022)
Ascites is the most common complication of end stage liver disease. Refractory ascites is considered a poor prognostic indicator and impacts quality of life, overall survival and contributes significantly to the cost associated with its management. Serial large volume paracentesis (LVP) and transjugular intrahepatic portosystemic shunt (TIPS) placement are the most utilized procedures for the management of refractory ascites and have their advantages and disadvantages. The pathophysiology of ascites in cirrhosis is multifactorial which makes management complex, requiring the consideration of multiple clinical and biochemical variables to guide the appropriate management. This article provides a broad overview of LVP and TIPS, with review of the latest clinical trials and meta-analyses to help guide the management of refractory ascites and improve patient outcomes.
Keywords: refractory ascites; large volume paracentesis; transjugular intrahepatic portosystemic shunt; cirrhosis; portal hypertension